Efecto de la ingesta de retinol en ratones albinos con cáncer inducido - Benavides R., Elena R. (2006)
The current study is an evaluation of Vitamin A supplement diet in female white mice Balb C53 inoculated with Sarcoma 180. The oral administration of a dose of 200 IU per day of Vitamin A in mice inoculated with sarcoma and divided in two groups, obtained a greater group B (vitamin A supplemented diet) mice survival curve than group A (normal diet) mice survival curve; however more studies are necessary to get a statistical significance. Liver concentration of catalasa was also quantified in three groups of mice: (1) healthy mice with normal diet; (2) sarcoma inoculated mice with normal diet; an (3) sarcoma inoculated mice with vitamin A supplement díet. It showed a significant difference of concentration of catalasa in group 2 in relation to group 1, unlike group 3 in relation to group 1. AH it indicates to us vitamin A anti-oxidant action, avoiding that the enzyme levels decreases. To determinate a possible existence of tumor expand inhibition related to vitamin A ingestion, a monitoring of the evolution of the tumor was made; registering group A and group B mice weights in different intervals until 22 days. Statistical difference didn't be finding.